2023
DOI: 10.3390/molecules28062558
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling of Acid-Leaching Solutions from Li-Ion Battery Waste Treatment through the Facile Synthesis of Magnetorheological Fluid

Abstract: The rapidly growing production and usage of lithium-ion batteries (LIBs) dramatically raises the number of harmful wastes. Consequently, the LIBs waste management processes, taking into account reliability, efficiency, and sustainability criteria, became a hot issue in the context of environmental protection as well as the scarcity of metal resources. In this paper, we propose for the first time a functional material—a magnetorheological fluid (MRF) from the LIBs-based liquid waste containing heavy metal ions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Analyzing the chemical compositions of the battery masses, it can be concluded that the composition of Material I differs significantly from the composition of the other materials, confirming a theory that cells from electric cars (EV) contain more nickel than cobalt, in comparison to cells from tablets, laptops and mobile phones-Table 2 [52,53].…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Analyzing the chemical compositions of the battery masses, it can be concluded that the composition of Material I differs significantly from the composition of the other materials, confirming a theory that cells from electric cars (EV) contain more nickel than cobalt, in comparison to cells from tablets, laptops and mobile phones-Table 2 [52,53].…”
Section: Methodsmentioning
confidence: 63%
“…For this reason, the industrial leaching method must take into account wide fluctuations in the composition of the leaching material, which in real conditions may be as follows (amount per ton of the processed battery mass): Al-35 kg; Co-69 kg; Cu-22 kg; Fe-20 kg; Li-24 kg; Mn-29 kg; Ni-100 kg; P-6 kg; F-29 kg; and C-340 kg. balt, in comparison to cells from tablets, laptops and mobile phones-Table 2 [52,53]. All materials contained a similar amount of carbon, ranging from 34.30% to 39.20%.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, much effort has been devoted to the development of nonflammable electrolytes, such as ionic liquid [ 26 , 27 , 28 ], fluorine-containing solvent [ 29 , 30 , 31 , 32 ], organic phosphate ester solvent [ 33 , 34 , 35 , 36 , 37 ] and solid-state electrolytes (SSEs) [ 38 , 39 , 40 , 41 , 42 ]. Although SSEs are considered as alternative electrolytes for the development of LMBs, the low ionic conductivity and inferior interface compatibility limit their further large-scale application in high-energy-density LMBs [ 43 , 44 , 45 , 46 , 47 ]. Due to the superior flame retardation and cost effectiveness, organic phosphate became one of many promising solvents in nonflammable electrolytes [ 48 , 49 , 50 ]; however, most phosphate ester flame retardants usually show poor compatibility with lithium metal anodes.…”
Section: Introductionmentioning
confidence: 99%